Chemical Composition and in-Vitro Evaluation of the Antimicrobial and Antioxidant Activities of Essential Oils Extracted from Seven Eucalyptus Species - Abdul Ghaffar; Muhammad Yameen; Shumaila Kiran; Shagufta Kamal; Fatima Jalal; Bushra Munir; Sadaf Saleem; Naila Rafiq; Aftab Ahmad; Iram Saba; Abdul Jabbar (Molecules, 2015)
Eucalyptus is well reputed for its use as medicinal plant around the globe. The present study was planned to evaluate chemical composition, antimicrobial and antioxidant activity of the essential oils (EOs) extracted from seven Eucalyptus species frequently found in South East Asia (Pakistan). EOs from Eucalyptus citriodora, Eucalyptus melanophloia, Eucalyptus crebra, Eucalyptus tereticornis, Eucalyptus globulus, Eucalyptus camaldulensis and Eucalyptus microtheca were extracted from leaves through hydrodistillation. The chemical composition of the EOs was determined through GC-MS-FID analysis. The study revealed presence of 31 compounds in E. citriodora and E. melanophloia, 27 compounds in E. crebra, 24 compounds in E. tereticornis, 10 compounds in E. globulus, 13 compounds in E. camaldulensis and 12 compounds in E. microtheca. 1,8-Cineole (56.5%), α-pinene (31.4%), citrinyl acetate (13.3%), eugenol (11.8%) and terpenene-4-ol (10.2%) were the highest principal components in these EOs. E. citriodora exhibited the highest antimicrobial activity against the five microbial species tested (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Aspergillus niger and Rhizopus solani). Gram positive bacteria were found more sensitive than Gram negative bacteria to all EOs. The diphenyl-1-picrylhydazyl (DPPH) radical scavenging activity and percentage inhibition of linoleic acid oxidation were highest in E. citriodora (82.1% and 83.8%, respectively) followed by E. camaldulensis (81.9% and 83.3%, respectively). The great variation in chemical composition of EOs from Eucalyptus, highlight its potential for medicinal and nutraceutical applications.